The concept of artistic endeavor of Russian writers of Kazakhstan. (Eurasian Journal of Philology Science and Education, 2015)
Interest in the Russian-language literature of Kazakhstan as a phenomenon of cultural space in the region explains the major trends of artistic conception and development of ethnic identity of cultural space by prose writers of Kazakhstan. The problem of the novel as an art form of national identity, especially the modern historical novel that based on specific language and cultural contacts of Kazakh and Russian culture, becomes the basis of research, which is developed sequential analysis of socio-cultural, historical and literary, artistic features of the formation anddevelopment of the Russian-language literature of Kazakhstan of the first half of the XX century: the works of writers as M.Simashko, Y.Dombrovski, I. Shukhov, Y.Schegolihin. The main purpose of this study is in consistent analysis of socio-cultural, historical and literary, artistic features of the formation and development of the Russian-languageliterature. The novelty consists in the analysis which represents not fully developed problems: theory and practice of functioning of Russian-speaking literary text within the literary process. The practical significance of the work is determined by the ability of using its main provisions, the findings and the results obtained in the development of various studies in terms of common literature dialogue, poetics and artistic originality of the prose works of Russian writers.
Keywords: Russian-language literature; the modern historical novel poetics and artistic originality of the literary text.